2016
DOI: 10.16966/2380-5536.127
|View full text |Cite
|
Sign up to set email alerts
|

HIV Care Providers’ Attitudes regarding Mobile Phone Applications and Web-Based Dashboards to support Patient Self-Management and Care Coordination: Results from a Qualitative Feasibility Study

Abstract: In-depth qualitative interviews were conducted with healthcare providers (HCPs) from five HIV medical care coordination teams in a large Los Angeles County HIV clinic, including physicians, nurses, and psychosocial services providers. HCPs reported on the potential utility, acceptability, and barriers for patient self-monitoring and notifications via mobile phones, and web-based dashboards for HCPs. Potential benefits included: 1) enhancing patient engagement, motivation, adherence, and self-management; and 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 19 publications
4
12
0
Order By: Relevance
“…First, there is interest and acceptability to use mHealth technologies to coordinate care between patients and providers (e.g. dashboards) [42**, 56*]. Dashboards can provide an easily interpretable, real-time overview of a patient’s ART tracking and other health indicators or behaviors (e.g.…”
Section: Challenges To Developing Delivering and Evaluating Mhealth mentioning
confidence: 99%
See 1 more Smart Citation
“…First, there is interest and acceptability to use mHealth technologies to coordinate care between patients and providers (e.g. dashboards) [42**, 56*]. Dashboards can provide an easily interpretable, real-time overview of a patient’s ART tracking and other health indicators or behaviors (e.g.…”
Section: Challenges To Developing Delivering and Evaluating Mhealth mentioning
confidence: 99%
“…This information can be used to provide tailored feedback to patients both at and between in-office appointments. Barriers to dashboard use include physician concerns about the privacy of patient information, ease of access/use, lack of coordination between dashboards and electronic medical records, and time restrictions both during and between patient visits [56*]. …”
Section: Challenges To Developing Delivering and Evaluating Mhealth mentioning
confidence: 99%
“…In the case of newly diagnosed and unstable HIV conditions, direct access to numbers was associated with bringing anxiety and uncertainty into care practices. In the study of Swendeman et al [18], clinicians suggested several ways in which mHealth devices should particularly address newly diagnosed patients and patients with comorbidities. Our data support the view that medication reminders, options to monitor blood results, etc, are particularly useful for these patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the EmERGE mHeaIth care pathway requires HIV patients to see their consultant face-to-face only every 12 months, while they can continuously monitor their blood results and maintain contact with their clinic through the smartphone app. Previous studies that have investigated the potential of mHealth in HIV care have suggested that such reductions in hospital visits are desirable for increasing the quality of life of PLWH [18]. The EmERGE project, as a whole, aims to validate the acceptability, usability, and effectiveness of the mHealth platform; assess its impact on patient self‐management and empowerment; analyze its cost-effectiveness; and disseminate the mHealth platform across various European health care settings as a sustainable, effective, safe, and economic modality for HIV care.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation